Low shear stress induces M1 macrophage polarization in murine thin-cap atherosclerotic plaques. (December 2015) - Seneviratne, Anusha N.; Cole, Jennifer E.; Goddard, Michael E.; Park, Inhye; Mohri, Zahra; Sansom, Stephen; Udalova, Irina; Krams, Rob; Monaco, Claudia
Abstract: Macrophages, a significant component of atherosclerotic plaques vulnerable to acute complications, can be pro-inflammatory (designated M1), regulatory (M2), lipid- (Mox) or Heme-induced (Mhem). We showed previously that low (LSS) and oscillatory (OSS) shear stress cause thin-cap fibroatheroma and stable smooth muscle cell-rich plaque formation respectively in ApoE-knockout (ApoE −/− ) mice. Here we investigated whether different shear stress conditions relate to specific changes in macrophage polarization and plaque morphology by applying a shear stress-altering cast to the carotid arteries of high fat-fed ApoE −/− mice. The M1 markers iNOS and IRF5 were highly expressed in macrophage-rich areas of LSS lesions compared to OSS lesions 6 weeks after cast placement, while the M2 marker Arginase-1, and Mox/Mhem markers HO-1 and CD163 were elevated in OSS lesions. Our data indicates shear stress could be an important determinant of macrophage polarization in atherosclerosis, with low shear promoting M1 programming.